Surgical outcomes of laparoscopic trachelectomy following supracervical hysterectomy: a multicenter study - Ayman Shehata Dawood; Heba Fouad Harras; Hossam Ramadan Moussa; Ahmed Saber Soliman (Korean Society of Obstetrics and Gynecology, 2022)
Objective To evaluate the feasibility, safety, and surgical outcomes of laparoscopic trachelectomy after supracervical hysterectomy. Methods This multicenter study was conducted at Tanta University, Benha University, and Aminah Laparoscopy Center (Benha, Egypt) from June 1, 2018 to October 31, 2021. Forty patients were recruited for this study and counseled on laparoscopic trachelectomy to treat their symptoms after supracervical hysterectomy. Furthermore, cervical biopsy was performed to detect and exclude any malignancy. Histopathological examination of cervical specimens was performed after surgery. Operative details and outcomes were recorded. Results The median age of the patients was 42 years (range, 38-47). The median body mass index was 25 years (range, 22-28). The median interval between hysterectomy and the clinical presentation was 4.40 years (range, 3.58-5.25). Most patients presented with abnormal vaginal discharge (40%) and bleeding (25%). Moreover, a cervical biopsy result revealed stump carcinoma in three cases (7.5%) that were excluded. The median operative time was 210 minutes (range, 170-220). The median blood loss was 270 mL (range, 220-320). Additionally, histopathological examinations revealed that chronic non-specific cervicitis was present in 54.05% of trachelectomy specimens. There were no significant differences between symptomatic and asymptomatic patients regarding operative outcomes, except adhesions, which were more significantly increased in symptomatic patients (P=0.015). Minimal complications, both operative and postoperative, were related to the procedure. Conclusion Although the operative time was long and adhesions were common during laparoscopic trachelectomy, the procedure was feasible and safe, with minimal complications.